Metagenomic Insights of the Microbial Community from a Polluted River in Brazil 2020 - Gil, Carolina O. P.; Pinto, Larissa Macedo; Nobre, Flavio F.; Thompson, Cristiane; Thompson, Fabiano; Tschoke, Diogo Antonio (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2021: Anais do XIV Simpósio Brasileiro de Bioinformática, 2021)
The water in the Metropolitan Region of Rio de Janeiro and in some municipalities in the Baixada Fluminense comes from the hydrological basin of the Guandu River (GR) and its potability is guaranteed by the Water Treatment Station of the Companhia Estadual de Águas e Esgotos. Along its route to the CEDAE dams, the GR suffers urban influences, being heavily impacted by receiving in natura effluents. To check the quality of the water in the GR, daily monitoring is carried out throughout its distribution network, including bacteriology. However, so far there is no metagenomics work to know what are the other microorganisms that exist in the GR that can cause diseases. This work aims to perform a metagenomic analysis of the GR to assess its diversity. Samples distributed in the catchment area of ​​CEDAE and drinking water were collected, submitted to DNA sequencing using Illumina. Quality control of Qpherd >30 sequences and joining of paired-end sequences forward and reverse with the Prinseq program. 203,951,644 sequences were obtained. The bacterial diversity index analysis did not show significant differences among the samples. The most abundant class was Betaproteobacteria. The cluster analysis showed to be significant for the drinking water sample to be grouped together with the raw water sample. The PCA-Biplot showed three clusters and which variables differentiate the samples, some genera having great contributions such as: Staphylococcus, Chthoniobacter and Riemerella.